Discovery of Novel Splice Variants and Regulatory Mechanisms for Microsomal Triglyceride Transfer Protein in Human Tissues - Suzuki, Takashi (Sci Rep, 2016)
Microsomal triglyceride transfer protein (MTP) is a unique lipid transfer protein essential for the assembly of triglyceride-rich lipoproteins by the liver and intestine. Previous studies in mice identified a splice variant of MTP with an alternate first exon. Splice variants of human MTP have not been reported. Using PCR approaches we have identified two splice variants in human tissues, which we have named MTP-B and MTP-C. MTP-B has a unique first exon (Ex1B) located 10.5 kb upstream of the first exon (Ex1A) for canonical MTP (MTP-A); MTP-C contains both first exons for MTP-A and MTP-B. MTP-B was found in a number of tissues, whereas MTP-C was prominent in brain and testis. MTP-B does not encode a protein; MTP-C encodes the same protein encoded by MTP-A, although MTP-C translation is strongly inhibited by regulatory elements within its 5′-UTR. Using luciferase assays, we demonstrate that the promoter region upstream of exon 1B is quite adequate to drive expression of MTP. We conclude that alternate splicing plays a key role in regulating cellular MTP levels by introducing distinct promoter regions and unique 5′-UTRs, which contain elements that alter translation efficiency, enabling the cell to optimize MTP activity.